1985
DOI: 10.1111/j.1471-0528.1985.tb03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Age as a prognostic factor in epithelial ovarian carcinoma

Abstract: Summary. One prognostic factor in epithelial ovarian cancer appears to be the patient's age at presentation. We have retrospectively analysed data from 2305 patients with this tumour in East Anglia during the period 1960–1980. The influence of age as a factor in survival was studied by comparing outcome in young patients between the ages of 15 and 35 (3.1% of all cases) with the outcome in the women over 35. The prognosis was significantly better in young patients, even when age correction is applied. This ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 4 publications
2
31
0
1
Order By: Relevance
“…However, studies on the prognostic implications of age and ovarian cancer are inconclusive. Although most reports have shown that younger women with ovarian cancer have an improved outcome compared to older women and have lower stage and more well-differentiated tumours (Smedley and Sikora, 1985;Plaxe et al, 1993;Thigpen et al, 1993;Rodriguez et al, 1994;Chan et al, 2003), others have found that age is not an independent prognostic factor after adjusting for tumour stage and grade (Massi et al, 1996;Duska et al, 1999). Moreover, the majority of these previous studies on ovarian cancer are based on single institution experiences, which contain inherent biases such as patient selection (Plaxe et al, 1993;Duska et al, 1999;Chan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies on the prognostic implications of age and ovarian cancer are inconclusive. Although most reports have shown that younger women with ovarian cancer have an improved outcome compared to older women and have lower stage and more well-differentiated tumours (Smedley and Sikora, 1985;Plaxe et al, 1993;Thigpen et al, 1993;Rodriguez et al, 1994;Chan et al, 2003), others have found that age is not an independent prognostic factor after adjusting for tumour stage and grade (Massi et al, 1996;Duska et al, 1999). Moreover, the majority of these previous studies on ovarian cancer are based on single institution experiences, which contain inherent biases such as patient selection (Plaxe et al, 1993;Duska et al, 1999;Chan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, owing to the low prevalence of young patients diagnosed with invasive ovarian cancer, these studies have also been limited by a small number of patients, inclusion of low malignant potential tumours, germ cell or sex cord stromal tumours, and unstaged cancers. European analyses on ovarian cancer incidence rates include studies carried out by Smedley and Sikora (1985), La Vecchia et al (1992), dos Santos Silva and Swerdlow (1995), Koper et al (1996), Nelson et al (1999). Given the limitations from prior reports, we proposed to perform a large population-based study to evaluate the clinico-pathologic characteristics between younger and older patients with epithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have estimated that 3-17% of all EOCs occur in women under 40 years of age. [3][4][5][6][7] In these patients, the preservation of the reproductive and endocrine functions is crucial. Therefore, fertility-sparing surgery has figured prominently in the consideration of appropriate gynecologic malignancy treatment.…”
Section: Discussionmentioning
confidence: 99%